Plasma 25-hydroxyvitamin D and rickets in infants of extremely low birthweight. Issue 11 (November 1982) - McIntosh, N; Livesey, A; Brooke, O G
Abstract : Rickets is now a well-known entity in infants of very low birthweight. In a 1-year period (1981) 8 of 15 neonatal survivors whose birthweight was less than 1000 g (extremely low birthweight) developed rickets despite high supplementation with ergo-calciferol, 2000 units a day. At the time of radiological diagnosis their postnatal age was 8 (range 5-14) weeks, and they all had normal or high plasma concentrations of 25-hydroxyvitamin D (mean 80 nmol/l, range 40-160 nmol/l). Although 4 infants received alfacalcidol which healed the rickets, in 4 infants the rickets healed spontaneously without change in treatment. The results suggest that inadequate vitamin D supplementation is not the cause of rickets in such infants.